The Populations' Resilience Toward the Policymaking Discrepancies in the Pandemic Covid-19 Period - Alsaqqa, Hatem H. (Frontiers in Public Health, 2021)
The world is in the midst of a crisis unlike any other in recent memory. COVID-19 is a pandemic that is urgent, global in scope, and has huge consequences. The policy sciences provide insights into unfolding trends, and this article uses the lessons of the literature to better understanding the policymaking shifts and population acceptability of COVID-19. The author attempts to investigate how policymakers’ emotions and narratives affect policy decisions and form policymaker-population relationships. The author addresses policymaking processes, transitions, interpretations of policy responses, policy implementation through multilateral topics and evaluating policy progress and failure. Trust is linked to cultural norms, values, and faiths in policy literature, and it is seen as a component of key social and economic policy outcomes. The author ends by identifying understudied facets of policymaking that need to be addressed during pandemics.